ABU YUSUF AND THE DEVELOPMENT OF ISLAMIC ECONOMIC THOUGHT - Ahmad Syahni; Muhammad Syafi'i Budi Santoso; Zakiyyah Ilma Ahmad; Muhammad Nasiruddin; Dimyati (Institut Agama Islam Negeri (IAIN) Bone, 2026)
This study examines the contribution of the classical Islamic economic thought of Abu Yusuf as presented in his monumental work, Kitab al-Kharaj. The primary objective of this study is to explore his concepts of public finance, taxation, and state intervention in market mechanisms to achieve social welfare. This study employs a qualitative approach using library research. The findings indicate that Abu Yusuf’s economic thought is grounded in the principles of justice, governmental accountability, and public welfare. The study reveals that Abu Yusuf pioneered the transition from a fixed tax system (misahah) to a proportional taxation system (muqasamah) based on taxpayers’ actual ability to pay. He also emphasized the state's responsibility to develop public infrastructure and regulate markets to prevent monopolistic practices (ihtikar). In conclusion, Abu Yusuf’s economic thought laid the foundation for a fiscal policy framework oriented toward public welfare, transparent management of the state treasury (Bayt al-Mal), and social justice. These ideas remain highly relevant and applicable to contemporary economic systems.